MEDIA EDUKASI PROMOSI KESEHATAN MELALUI FILM DALAM MENUMBUHKAN PENGETAHUAN, SIKAP DAN PERILAKU KESEHATAN REPRODUKSI PADA REMAJA - Besar Tirto Husodo; Novia Handayani; Ulfa Velia Aisyiyah Purnamawati (Jurnal Kesehatan Masyarakat (Undip), 2021)
One way to provide adolescent reproductive health education is through film media. Films are a collection of events that occur in unique human life and are poured into the screen. Signs produced by humans are used as visuals that can be seen from various perspectives and provide a separate message for each individual. “Dua Garis Biru” is a form of reproductive and sexual health promotion in form of movie for teenager, which is an attractive ways for teenager to understand the information about reproductive and sexual health. This study aims to explain how the understanding of reproductive health content delivered through the movie "Dua Garis Biru" to teenager at Junior High School X Semarang City. This research was conducted using quantitative descriptive method and cross sectional design. The population in this research were 567 students from 8th and 9th grade of 2020/2021 academic year who attended Junior High School  X Semarang City. The total of sample in this study is 85 respondents who were determined through the calculation of the Slovin formula. The results showed that the knowledge and attitudes of respondents who are already good after receiving information on adolescent reproductive health content through “Dua Garis Biru” were 58.8% and 68.2%. “Dua Garis Biru” can be used as a media in providing adolescent reproductive health education in schools.